The power of believing you can get smarter - Outes-León, Ingo,Sanchez, Alan,Vakis, Renos (World Bank Group, Poverty and Equity Global Practice, 2020)
This paper evaluates the academic impact of a growth-mindset intervention on students starting the secondary level in public schools in urban Peru. Expande tu Mente is a 90-minute school session aimed at instilling the notion that a person's own intelligence is malleable. Students in schools randomly assigned to treatment showed a small improvement in math test scores and educational expectations, with a large and sustained impact in test scores among students outside the capital city. At a cost of USD 0.20 per pupil, Expande tu Mente was highly cost-effective. The results show the potential that brief growth-mindset interventions have for developing countries
10.1596/1813-9450-9141
Keywords: Graue Literatur; education; disadvantaged students; growth mindset; metacognition; academic support; Peru